1997
DOI: 10.1111/j.1365-2621.1997.tb04020.x
|View full text |Cite
|
Sign up to set email alerts
|

Dried Soy Tofu Powder Effects on Frankfurters and Pork Sausage Patties

Abstract: Regular frankfurters treated with tofu powder had decreased fat with no significant differences in color, texture, or overall acceptability compared to a control by sensory analysis. Lean frankfurters with tofu powder had lower moisture and color, better texture, and overall acceptability with no flavor differences from controls. Except for fracturability, there were no differences in texture-related parameters by Texture Profile Analysis (TPA) between regular and control frankfurters but treated lean frankfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
4
15
0
Order By: Relevance
“…Figure 1 shows controls had highest TBARS value than treatments, however, the value increased (p<0.05) in all samples with the increase of storage periods. These findings are agreement with the findings of Ho et al (1997) who reported that chicken sausages treated with carragreenan, soy protein concentrate or antioxidants did not show difference in initial TBARS, but were increased over storage. At the end of the storage, the lowest TBARS were found in T 3 sample (0.62 mg malonaldehyde per kg), and this value was much lower than the threshold value of TBARS is around 2.0 mg maloaldehyde/kg (Witte et al 1970).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Figure 1 shows controls had highest TBARS value than treatments, however, the value increased (p<0.05) in all samples with the increase of storage periods. These findings are agreement with the findings of Ho et al (1997) who reported that chicken sausages treated with carragreenan, soy protein concentrate or antioxidants did not show difference in initial TBARS, but were increased over storage. At the end of the storage, the lowest TBARS were found in T 3 sample (0.62 mg malonaldehyde per kg), and this value was much lower than the threshold value of TBARS is around 2.0 mg maloaldehyde/kg (Witte et al 1970).…”
Section: Resultssupporting
confidence: 83%
“…Matlock et al (1984) also reported textural scores decline with the extension of storage period, and that were more visible in carragreenan control and carragreenan-soy incorporated products. Ho et al (1997) reported that the soy protein concentrate results in off-flavour in reduced-fat sausage products after 4 week of refrigeration storage. The overall acceptability of nugget samples also followed the same pattern that observed for other sensory attributes.…”
Section: Resultsmentioning
confidence: 99%
“…Gel strength is a highly controversial texture parameter, as several authors have found contradictory results. Ho et al (1997) did not find any significant difference in gel strength and cohesiveness between regular frankfurters and those made with tofu (a soy product). Chin et al (2000) found the similar textural features (hardness and gel strength) in regular bologna (30% lipids) and bologna made with 2% isolated soy protein/1% konjac.…”
Section: Gel Strength Of Emulsified Sausage Made With Argentine Croakmentioning
confidence: 58%
“…Soy proteins are known for water-binding, fat-binding, and supporting high emulsion stability (Chin et al, 2000); hence, soy protein isolates (SPI) and concentrates are widely used in the preparation of chopped meats (Gordon and Barbut, 1991). However, addition of SPI occasionally gives less desirable palatability and allergen issue to meat products (Ho et al, 1997), and hence there are regulations to restrict their use in meat products. In the United States, the maximum quantity of SPI that can be added to sausage types of products is only 2% (Belloque et al, 2002).…”
Section: Introductionmentioning
confidence: 99%